Peran Metode Cooperative Learning dalam Meningkatkan Kemampuan Berpikir Kritis dan Problem Solving Siswa Sekolah Dasar - Ziyad, Thoriq Bin (Yayasan Pendidikan Intan Cendekia, 2023)
This study aims to analyze the impact of the Cooperative Learning method on the development of students' critical thinking and problem-solving skills in elementary education. Cooperative Learning is an instructional approach that encourages active interaction among students in small groups to achieve shared learning objectives, potentially enhancing deeper thinking skills. The research employs a quasi-experimental method with a pre-test and post-test design, involving fifth-grade students from an elementary school. Data collection includes critical thinking tests, classroom observations, and interviews with teachers to assess the effectiveness of the Cooperative Learning strategy. The findings indicate a significant improvement in students' critical thinking and problem-solving abilities following the implementation of this method. Social interactions within learning groups contribute to students' ability to develop arguments, validate ideas, and find creative solutions to given problems. These results suggest that Cooperative Learning can be an effective strategy for fostering critical thinking skills from an early age. Thus, this approach is recommended for widespread implementation in collaborative learning environments at the elementary level